ANXIETY AND ITS RELATIONSHIP TO THE PERFORMANCE OF DIRECTED VOLLEYBALL SERVE ACCORDING TO DIFFERENT PERFORMANCE METHODS (American Journal of Pedagogical and Educational Research, 2023)
Research Problem: There are psychological pressures that lead to disorders, including the phenomenon of anxiety, which is a prevalent issue in our times. The educational process affects the students' personalities, leading them to live in constant anxiety. Anxiety is a deep feeling characterized by fear, dissatisfaction, and distress, with varying degrees of response. Students in secondary stages experience anxiety related to various variables, such as the performance of directed volleyball serves according to different methods. After the serve, the ball is put into play after the referee's whistle to address the problem and earn points.